New Member of the Herpesvirus Group Isolated from Wild Cottontail Rabbits - Hinze, Harry C. (1971)
A viral agent has been isolated from naturally infected wild cottontail rabbits (Sylvilagus floridanus). The virus appears to have the general physical, chemical, and biological properties of the herpesvirus group. It differs significantly in host range and antigenic structure from the previously recognized herpesviruses and is proposed as a new member of this group of viruses. The name of Herpesvirus sylvilagus is suggested for the agent.